Responsibility toward the “Other”: A critical examination of Levinas's ethical philosophy - Imran, Muzzamel Hussain (Metaphilosophy, 2025)
Emmanuel Levinas introduced a radical rethinking of subjectivity that challenges the foundational assumptions of Western philosophy and conventional ethics. He contends that traditional moral frameworks are rooted in egoism, privileging autonomy, self‐interest, and self‐actualization while marginalizing the ethical significance of the Other. Levinas reorients philosophy away from a self‐centered conception of the subject toward one grounded in ethical responsibility and relationality. He argues that our responsibility toward the Other is infinite, asymmetrical, and inescapable—it is not chosen but imposed by the mere presence of the Other. Drawing on the catastrophic failures of modernity, including genocide, war, and systemic injustice, Levinas critiques the insufficiency of traditional rationalism to confront such violence. His work offers a profound shift from ontology to ethics, from being to responsibility. This article critically explores these arguments and examines their implications for rethinking ethical relations and the foundations of social and political structures.